下面 "结论" 中, 正确的是
$\text{A.}$ 若 $\sum_{n=1}^{\infty} u_n$ 与 $\sum_{n=1}^{\infty} v_n$ 都发散, 则 $\sum_{n=1}^{\infty}\left(u_n+v_n\right)$ 发散
$\text{B.}$ 若 $\sum_{n=1}^{\infty}\left(u_n+v_n\right)$ 收敛, 则 $\sum_{n=1}^{\infty} u_n$ 与 $\sum_{n=1}^{\infty} v_n$ 都收敛
$\text{C.}$ 若 $\sum_{n=1}^{\infty} u_n$ 与 $\sum_{n=1}^{\infty} v_n$ 都收敛, 则 $\sum_{n=1}^{\infty}\left(u_n+v_n\right)$ 都收敛
$\text{D.}$ 若 $\sum_{n=1}^{\infty} u_n$ 收敛, $\sum_{n=1}^{\infty} v_n$ 发散, 则 $\sum_{n=1}^{\infty}\left(u_n+v_n\right)$ 的收敛性不确定